Chess digital clock - Rosmira, Roslan (2008)
The purpose of my project is to design and implement of the Chess Digital Clock. The project employs ISE software (ISE Design Suite 10.1) and implementation on Field-Programmable Gate Arrays (FPGAs) Xilinx board. It is a new technique for testing the interconnects of an arbitrary design mapped into an FPGA. Field-Programmable Gate Arrays (FPGAs) have become one of the key digital circuit implementation media over the last decade. A crucial part of their creation lies in their architecture, which governs the nature of their programmable logic functionality and their programmable interconnect. The experimental result on various benchmarks using the ISE software is on its simulation. The software is designed using VHDL code. Digital circuit modeling with hardware description languages (HDLs) is the key to modern design of integrated circuits (ICs). The state-of-the-art technique of designing complex digital systems and integrated circuits is to apply an HDL-based CAD approach, in which a high-level, text-based, abstract description of the circuit is created, then synthesized to a hardware implementation in a selected technology, and finally verified for its functionality and timing.